Rocuronium-Induced Anaphylactic Shock during Elective Septoplasty: A Case Report - Bajracharya, Nitendra Raj; Shrestha, Saurav; Dangol, Shova; Paudel, Rabi; Bishwokarma, Pushkar; Shrestha, Surendra Man (Medical Journal of Armed Police Force Nepal, 2025)
Introduction: Perioperative anaphylaxis is a rare but potentially fatal complication during anesthesia. Rocuronium, a commonly used neuromuscular blocking agent, is a leading cause of intraoperative anaphylaxis. Early recognition and prompt management are crucial to reduce morbidity and mortality in an anaesthetized patient. Case presentation: We report a case of 14-year-old female with Hashimoto’s thyroiditis and dissociative disorder undergoing elective septoplasty for right antrochoanal polyp. Following induction with midazolam, fentanyl, propofol, rocuronium, and the patient developed grade III anaphylaxis characterized by severe hypotension, tachycardia, generalized rash, lip swelling, and increased airway pressure immediately after endotracheal intubation. Rocuronium was suspected as the trigger. Immediate management with intravenous epinephrine boluses (300 μg ×2), fluid resuscitation (2 liters normal saline), hydrocortisone and initiation of an epinephrine infusion (0.1 μg/kg/min) was done and surgery was postponed. The patient was transferred to the intensive care unit (ICU) for close monitoring. Epinephrine infusion was tapered off and she was successfully extubated the next day, and discharged to the ward on the third day without neurological or respiratory sequelae. Conclusions: This case emphasizes on the critical importance of early recognition of rocuronium-induced anaphylaxis, rapid administration of epinephrine and aggressive supportive care. Despite the incidence of such reactions remains low, the high fatality rate necessitates preparedness during anesthesia.